Exchange rate and trade balance relationship : empirical study in Cambodia, Thailand and vietnam - Kong, Michelle Ping Ping (Universiti Malaysia Sarawak, (UNIMAS), 2012)
The purpose of this study is to investigate the relationship between exchange rate and trade balance in both short run and long run for three Indo-China countries, namely Cambodia, Thailand and Vietnam for the period from 1994 (IV) to 2010 (IV). The stationary test, ARDL bounds test and Granger causality have been used in the study. The empirical results indicate that although there is no long run relationship found between the exchange rate and trade balance in Cambodia, Thailand and Vietnam but the exchange rate does have impact on trade balance in these countries in the short run. These findings are important to policy makers to adopt an appropriate exchange rate regime to obtain a desired effect of trade balance.